Crop Species Mechanisms and Ecosystem Services for Sustainable Forage Cropping Systems in Salt-Affected Arid Regions - Ashilenje, Dennis S.; Amombo, Erick; Hirich, Abdelaziz; Kouisni, Lamfeddal; Devkota, Krishna P.; El Mouttaqi, Ayoub; Nilahyane, Abdelaziz (Frontiers in Plant Science, 2022)
Soil salinity limits crop productivity in arid regions and it can be alleviated by crop synergies. A multivariate analysis of published data (n = 78) from arid and semiarid habitats across continents was conducted to determine the crop species mechanisms of salinity tolerance and synergies relevant for designing adapted forage cropping systems. Halophyte [Cynodon plectostachus (K. Schum.) Pilg.] and non-halophyte grasses (Lolium perenne L. and Panicum maximum Jacq.) clustered along increasing soil salinity. Halophytic grasses [Panicum antidotale Retz. and Dicanthum annulatum (Forssk.) Stapf] congregated with Medicago sativa L., a non-halophytic legume along a gradient of increasing photosynthesis. Halophytic grasses [Sporobolus spicatus (Vahl) Kunth, and Cynodon plectostachyus (K. Schum.) Pilg.] had strong yield-salinity correlations. Medicago sativa L. and Leptochloa fusca L. Kunth were ubiquitous in their forage biomass production along a continuum of medium to high salinity. Forage crude protein was strongly correlated with increasing salinity in halophytic grasses and non-halophytic legumes. Halophytes were identified with mechanisms to neutralize the soil sodium accumulation and forage productivity along an increasing salinity. Overall, halophytes-non-halophytes, grass-forbs, annual-perennials, and plant-bacteria-fungi synergies were identified which can potentially form cropping systems that can ameliorate saline soils and sustain forage productivity in salt-affected arid regions.